Raja’s Banana (Musa textilia) Stems Fiber Rope Tensile Endurance - Alin Maya Sari; Saipul Bahri Daulay; Sulastri Panggabean (Universitas Sumatera Utara, 2014)
Raja’s banana fibers have the best tensile endurance between the others. The characteristic, could be used making rope that can be used for binding, pulling, trapping, tethering, hanging and others in accordance with the rope usefulness. The research was aimed to know the endurance of Raja’s banana fiber rope with and without NaOH solution on the rope tensile test. Results of the research indicated that the two, three and four twists with and without NaOH 5% during two hour gave the different results of tensile strength, strain, deformation, elasticity and flexing. The highest result of tensile strength was on the three twist condition (with treatment) i.e. 515,92×105 Nm-2. The highest result of strain was on the three twist condition (with treatment) i.e. 1,98. The highest result of deformation was on the three twist condition (with treatment) i.e. 0,099 m. The highest result of elasticity was on the four twist condition (with treatment) i.e. 318,47×105 Nm-2. And the highest result of flexing was on the four twist condition (with treatment) i.e. 64%. Key words: Raja’s banana stems fiber, rope, twisting, NaOH, tensile test.